2006
DOI: 10.1136/hrt.2005.082115
|View full text |Cite
|
Sign up to set email alerts
|

Role of regional mechanical dyssynchrony as a determinant of functional mitral regurgitation in patients with left ventricular systolic dysfunction

Abstract: The degree of FMR is associated mainly with mitral deformation indices. The regional dyssynchrony also has an independent association with ERO but with a minor influence; however, it is not a determinant of FMR in patients with ischaemic LV dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 20 publications
3
55
1
Order By: Relevance
“…In this study with dilated cardiomyopathy patients, the difference between time to peak systolic myocardial strain of myocardial segments adjacent to medial and lateral papillary muscles was found to be related with FMR. Similarly, in another recent study, regional myocardial dyssynchrony was found to be related with FMR (16).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…In this study with dilated cardiomyopathy patients, the difference between time to peak systolic myocardial strain of myocardial segments adjacent to medial and lateral papillary muscles was found to be related with FMR. Similarly, in another recent study, regional myocardial dyssynchrony was found to be related with FMR (16).…”
Section: Introductionsupporting
confidence: 58%
“…CRT reduces the amount of FMR in patients with left ventricular (LV) systolic failure (9)(10)(11)(12)(13)(14). Studies have shown that the severity of FMR was correlated with the papillary muscle dyssynchrony (PMD) (15)(16)(17)(18). Moreover, PMD was found to predict the improvement of FMR after CRT and help make the choice of treatment options such as CRT with or without mitral valve repair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of tension exerted on the leaflets mainly depends on the entity of PMs displacement, which is the actual cause of the impaired coaptation and valve regurgitation observed in IMR. Tethering can have a symmetric or asymmetric pattern reflecting the direction of PM displacement vector, the localization of myocardial infarction zone and the severity of global ventricular dysfunction (15,16). Normally PMs provide a number of chordae that are attached to both leaflets, anterior and posterior, but with a substantial difference in case of symmetric or asymmetric tethering shape.…”
Section: Diagnosis and Considerations Of Geometric Parameters Conditimentioning
confidence: 99%
“…This results in a vicious circle, with both LV dilatation and FMR acting as self-perpetuating processes. CRT may contribute to the reduction of FMR and reversing LV dilation [6,7].Functional mitral regurgitation, observed in patients with ischaemic and non-ischaemic cardiomyopathy, results from an imbalance between LV closing forces and mitral valve tethering forces, and resultant deformation of mitral valve geometry [2,8]. FMR improvement (FMRI) after CRT implantation is a multistage process being modulated by an array of factors [2,9].…”
mentioning
confidence: 99%